Lower Central Fat Increase Risk of One-Year Muscle Mass Loss in Menopausal Women - Ying-Chou Chen; Wei-Che Lin; Tien-Tsai Cheng; Jia-Feng Chen; Shan-Fu Yu; Chung-Yuan Hsu (Hindawi Limited, 2020)
Background. Hormonal changes had been found in menopausal women. Muscle and bone mass decline after menopause and with aging, increasing the risk for sarcopenia and osteoporosis in later life. Only a few studies suggest that menopausal hormonal changes have an effect on the decline in muscle mass. Objectives. This study aimed at evaluating the risk of muscle mass loss in menopausal women. Materials and Methods. Menopausal women from routine physical health examination were eligible for this study. Muscle mass was determined using dual-energy X-ray absorptiometry at baseline and 1 year later. All of the patients underwent the assessments for liver and kidney function, diabetes, and hypertension, and associated comorbidities were recorded. Results. A total of 172 patients were enrolled. 70 patients had muscle loss at 1 year, and the other 102 did not had loss. The mean age was 70.26±9.93 years at the muscle loss group, while 69.25±10.50 at the nonprogress group (p=0.531). The mean body mass index was 22.96±1.91 kg/m2 at the muscle loss group, while 23.33±3.71 kg/m2 at the nonprogress group (p=0.433). The baseline trunk limb fat mass ratio was 1.01±0.20 in the muscle loss group and 1.12±0.26 in the no muscle loss (p=0.004). Using muscle mass loss as the outcome, logistical regression analysis showed that a baseline trunk limb mass ratio could predict muscle loss, and a higher baseline trunk limb mass ratio was associated with less muscle loss, while a lower trunk limb mass ratio was associated with increased muscle mass loss (p=0.01). Conclusion. This is the first study to investigate the risk of muscle mass loss in menopausal women. Menopausal women with higher central fat had less muscle mass loss, while lower central fat was a risk factor for muscle mass loss. Chronic kidney disease was also a risk factor for muscle mass loss in menopausal women in this study.